2020
DOI: 10.1111/bju.15033
|View full text |Cite
|
Sign up to set email alerts
|

Utility of multiparametric magnetic resonance imaging in the risk stratification of men with Grade Group 1 prostate cancer on active surveillance

Abstract: ObjectiveTo assess if the adoption of multiparametric magnetic resonance imaging (mpMRI) in active surveillance (AS) has improved the identification of occult higher-grade prostate cancer (PCa). Patients and MethodsWe retrospectively identified men from the Johns Hopkins AS registry enrolled since 2013 (year of mpMRI adoption) with Grade Group (GG) 1 PCa and who underwent a single mpMRI. Men in this group were dichotomised by the presence (n = 207) or absence (negative mpMRI, n = 225) of one or more lesions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…We also note that in previous studies, lesions in patients with GG 1 PCa were reported to be largely invisible on mpMRI [ 16 17 18 ]. Therefore, although several studies have reported mpMRI to be useful for the selection of candidates appropriate for AS [ 19 20 ], mpMRI may, in fact, be reliable only for candidates with GG ≥2 lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also note that in previous studies, lesions in patients with GG 1 PCa were reported to be largely invisible on mpMRI [ 16 17 18 ]. Therefore, although several studies have reported mpMRI to be useful for the selection of candidates appropriate for AS [ 19 20 ], mpMRI may, in fact, be reliable only for candidates with GG ≥2 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of mpMRI for PCa, mpMRI and PI-RADS scoring have been used as screening criteria for AS [ 7 19 20 ]. Zhai et al [ 19 ] reported that the pooled estimates of PI-RADS scores of 4 or 5 predicted adverse pathologic features on examination of RP specimens among AS candidates, based on the PRIAS criteria, with a sensitivity, specificity, positive predictive value, negative predictive value, and area under the curve of 0.77, 0.63, 0.72, 0.68, and 0.77, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk calculators, such as the Canary Prostate Active Surveillance Study risk calculation 87 , the Johns Hopkins model 88 and the PRIAS model 89 have been developed in an effort to address this need. These AS risk calculators can selectively predict men at risk of progression and balance reclassification detection with the number of surveillance biopsies by incorporating the serial measurement of the monitoring tools into the prediction model (for example, patient age, prostate volume, PSA, time since diagnosis, number of previous biopsies and all previous biopsy results) [90][91][92][93][94] .…”
Section: Research Need Number 2 Develop Indicators To Better Stratifymentioning
confidence: 99%
“…Significant sampling error and morbidity associated with prostate biopsy complicates differentiation between aggressive and indolent disease so that post-radical prostatectomy (RP) upgrading and upstaging is common [5][6][7]. Recently, multi-parametric magnetic resonance imaging (mpMRI) showed improvements in risk stratification of men on AS and was recommended for enhancing enrolment and monitoring decision [8][9][10].…”
Section: Introductionmentioning
confidence: 99%